Transferrin in patients with multiple sclerosis: a comparison among various subgroups of multiple sclerosis patients - Zeman, D; Adam, P; Kalistová, H; Sobek, O; Kelbich, P; Andel, J; Andel, M (Acta neurologica Scandinavica, 2000)
OBJECTIVES: To compare cerebrospinal fluid (CSF) and serum transferrin (Tf) concentrations, transferrin quotient and index in various subgroups of MS patients. MATERIAL AND METHODS: CSF and serum transferrin concentrations, transferrin quotient QTf (i.e. CSF transferrin/serum transferrin x 10(3)) and index (QTf/Qalbumin) were determined in a group of 51 patients with clinically definite or probable multiple sclerosis (MS). Patients were subdivided according to the disease form (relapsing-remitting = RR, secondary progressive = SP, primary progressive = PP; patients with RR form were further subdivided into those in the attack and those in remission), disease severity (EDSS 0-5.5, EDSS 6.0-10.0), its treatment (non-treated - including patients treated with vitamins and/ or vasodilators only, treated - i.e. glucocorticoids and/or immunosuppressants and/or (exceptionally) beta-interferon), disease duration (0-2 years, >2-10 years, > 10 years) and sex. Correlation of transferrin values with age was also performed. RESULTS: Serum transferrin was somewhat lower and significantly more frequently subnormal in PP patients in comparison with the SP form and the RR form in remission. Transferrin index was significantly higher in the PP form than in the RR as well as the SP form. Transferrin quotient was significantly more frequently subnormal in patients in remission compared to those in the attack of the RR disease. CSF transferrin as well as transferrin quotient were more frequently subnormal in patients with short disease duration (0-2 years) than in patients with longer disease duration; these parameters, however, correlated also significantly with age. CSF transferrin and transferrin quotient were higher in male than in female patients. CONCLUSION: The authors conclude that evaluation of transferrin in MS patients - along with albumin - may help to differentiate among various MS subgroups, since there are significant differences among RR, SP and PP forms. For this purpose, however, other CSF protein fractions should be evaluated in parallel in order to obtain more complex information and to establish a panel of examinations enabling multiple statistical analyses. Transferrin evaluation in MS may also be of significant theoretical interest, since transferrin is known to be involved in the regulation of iron metabolism and it may have a protective role against the oxidative stress. Moreover, transferrin is a growth factor important for proliferation of activated T lymphocytes. By means of the use of transferrin quotient and especially transferrin index, it may be possible to estimate the proportion of intra-CNS-synthesized transferrin and/or rate of specific transferrin transport across the blood-CSF barrier. Further studies are, however, needed for such an evaluation.
Keywords: Age Factors; antioxidancia; mužské pohlaví; Multiple Sclerosis, Chronic Progressive; Male; Humans; Female; Blood-Brain Barrier; Transferrin; analýza rozptylu; lidé; Antioxidants; chronicko-progresivní roztroušená skleróza; ženské pohlaví; stupeň závažnosti nemoci; transferin; relabující-remitující roztroušená skleróza; Multiple Sclerosis, Relapsing-Remitting; Severity of Illness Index; hematoencefalická bariéra; Analysis of Variance; roztroušená skleróza; Multiple Sclerosis; věkové faktory